2013
DOI: 10.1103/physrevx.3.041009
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Coherence Encoded in an “Air-Laser” Spectrum of Nitrogen Molecular Ions in an Intense Laser Field

Abstract: We investigate lasing action in aligned nitrogen molecular ions (N 2 þ) produced in an intense laser field. We find that, besides the population inversion between the B 2 AE u þ À X 2 AE g þ states, which is responsible for the observed simulated amplification of a seed pulse, a rotational wave packet in the ground vibrational state (v ¼ 0) of the excited electronic B 2 AE u þ state has been created in N 2 þ. The rotational coherence can faithfully encode its characteristics into the amplified seed pulses, ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 23 publications
2
66
1
1
Order By: Relevance
“…[20,21]. The femtosecond laser beam (1 kHz, 800 nm, ~40 fs) produced by a commercial Ti:sapphire laser system (Legend Elite-Duo, Coherent, Inc) was divided into two arms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[20,21]. The femtosecond laser beam (1 kHz, 800 nm, ~40 fs) produced by a commercial Ti:sapphire laser system (Legend Elite-Duo, Coherent, Inc) was divided into two arms.…”
Section: Methodsmentioning
confidence: 99%
“…Pump-probe measurements based on these pulses can provide a sufficient temporal resolution to reveal the rotational dynamics of many kinds of molecules such as the nitrogen molecule investigated in this work. Second, the bandwidth of the strong-field-ionization induced molecular lasing spectrum is typically on the scale of ~0.1 nm, providing a sufficient spectral resolution to distinguish the different rotational states [15,21]. In our point of view, the combination of these advantages opens new possibilities for investigation of 6 strong field molecular physics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we show that the nitrogen ion laser can be applied to investigate the rotational coherences of molecular wave packets. The ultrashort pump laser pulses not only generate the population inversion between the excited state 2 Σ + and the ground states 2 Σ + of 2 + , which is responsible for the simulated amplification seeded by an external pulse, but also creates a rotational wave packet in the ground vibrational state (υ = 0) of the excited electronic state 2 Σ + [4][5]. The rotational coherences of 2 + will faithfully encode its characteristics into the amplified seed pulses.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, Zhang et al observed that the rotational coherence of the molecular ions can encode its characteristics into the air laser [16]. The coherent rotational wave packet of the molecular ions was achieved either by ionization-induced alignment [17] or by Raman-type interaction of the pump laser with the molecules [18], or a combination of the two.…”
Section: Introductionmentioning
confidence: 99%